Examining the Impact of Organizational Culture on Customer Centricity in Organizations:An Analysis - Bedarkar, Madhura; Pandita, Deepika; Agarwal, Ravi; Saini, Rupinder (Prabandhan: Indian Journal of Management, 2016)
The aim of this paper was to develop a theoretical framework to understand the effect of organizational culture, customer centricity, and knowledge management on organizational effectiveness. An organization's culture is reflected by its vision and values. A customer centric organization has its core values centered on constantly striving towards serving the customers better. Organizations practice customer relationship management (CRM) to improve customer satisfaction and loyalty. Relevant knowledge about the customers is most important to understand their needs. Knowledge management plays an important role here. Knowledge about the product, customer, brand, and competition are essential for the employees to understand how the customers feel about an organization's products/services and hence, organizations can innovate further to attain customer delight. A customer-centric culture in an organization leads to customer-centric knowledge creation and thus, improves organizational effectiveness through an increase in customer satisfaction.